2-[(E)-2-(4-Ethoxyphenyl)ethenyl]-1- methylquinolinium 4-fluorobenzenesulfonate - Hoong, Kun Fun; Kobkeatthawin, Thawanrat; Ruanwas, Pumsak; Ching, Kheng Quah; Chantrapromma, Suchada (International Union of Crystallography, 2014)
In the structure of the title salt, C20H20NO+C6H4FO3S, the 4-(ethoxyphenyl)ethenyl unit is disordered over two positions with a refined site-occupancy ratio of 0.610 (6):0.390 (6). The cation is nearly planar, the dihedral angle between the quinolinium and benzene rings being 6.7 (4) and 1.7 (7) for the major and minor components, respectively. The ethoxy group is essentially coplanar with the benzene ring [C—O—C—Cmethy = 177.1 (8) and 177.8 (12) for the major and minor components, respectively]. In the crystal, cations and anions are linked into chains along the b-axis direction by C—H Osulfonyl weak interactions. These chains are further connected into sheets parallel to (001) by C—H Osulfonyl weak interactions. The chains are also stacked along the a axis through – interactions involving the quinolinium and benzene rings [centroid–centroid distances = 3.636 (5) A ° for the major component and 3.800 (9) A ° for the minor component]. C—H interactions are also present.